PASAR PUBLIK MAYESTIK - Sebastian Tanuwidjaja; Sidhi Wiguna Teh (Jurusan Arsitektur dan Perencanaan, 2020)
A third place is needed by various groups of human. This serves as entertainment for the routine of human activity in the modern times. Where Their lives are divided by the first place that becomes their home and the second place where they running daily work activities. The Project is located on Jalan Tebah, Kebayoran Baru which is famous for its trading. Activities around the site are dominated by trade activities, other activities are school, office and housing activities. The purpose of this project is to facilitate the community to socialize from all groups of people through trading activities, the role of the community in this project is as a user who is divided into the role of traders who work as entrepreneurs and buyers. It also aims to support the Sustainable Development Goals program regarding equality of social status. With an individualist lifestyle due to demands of time-consuming work and humans need primary needs, therefore the Mayestik Public Market was formed to accommodate the needs of clothing and food and recreation with a third place concept. The market program is divided into 2 parts, namely wet and dry areas. In the wet area there are Food Street, Fresh Market, Mini Market and Bar, while in the dry area there are Bazaar, Online Marketplace, and Barbershop. There are also other programs to support the third place and self-development activities with Library, Artspace, Culinary Workshop, and Public Space. This place can be used for all people without paying, hoping to unite people from all groups of people without looking at each other's social status and interacting with one another as they should. Keywords: Kebayoran Baru; Market; Needs; Third Place AbstrakSebuah tempat ketiga sangat dibutuhkan oleh berbagai kalangan manusia. Hal ini berfungsi sebagai hiburan terhadap rutinitas kegiatan manusia pada masa modern. Dimana kehidupan mereka terpecah pada sebuah tempat pertama yang menjadi rumah dan tempat kedua yang menjadi tempat kegiatan bekerja mereka sehari-hari. Lokasi Proyek terletak di Jalan Tebah, Kebayoran Baru yang terkenal dengan area perdagangan. Aktivitas di sekitar tapak didominasi aktivitas perdagangan, aktivitas lainnya terdapat aktivitas sekolah, perkantoran dan perumahan. Tujuan dari proyek ini adalah untuk memfasilitasi masyarakat untuk bersosialisasi dari semua kalangan melalui aktivitas perdagangan, peran masyarakat pada proyek ini adalah sebagai user yang terbagi menjadi peran pedagang yang bekerja sebagai wirausaha yang dan pembeli. Hal ini juga bertujuan mendukung program Sustainable Development Goals perihal kesetaraan status sosial. Manusia membutuhkan kebutuhan primer dan dengan gaya hidup manusia modern yang individualis akibat tuntutan pekerjaan yang memakan waktu, oleh sebab itu dibuatlah sebuah Pasar Publik Mayestik yang dapat mewadahi kebutuhan sandang dan pangan serta rekreasi dengan konsep tempat ketiga. Program pasar dibagi menjadi 2 bagian, yaitu area basah dan area kering. Dalam area basah terdapat program Food Street, Fresh Market, Mini Market, dan Bar, sedangkan pada area kering terdapat program Bazaar, Online Marketplace, dan Barbershop. Terdapat juga program lainnya untuk mendukung konsep tempat ketiga dan aktivitas pengembangan diri berupa Library, Artspace, Culinary Workshop, dan Public Space. Tempat ini dapat digunakan untuk semua kalangan manusia tanpa harus berbayar, dengan harapan dapat menyatukan manusia dari semua kalangan tanpa melihat status sosial masing-masing dan berinteraksi satu dengan lainnya seperti seharusnya.